If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 + -9b = -6b + -17 Reorder the terms: 13 + -9b = -17 + -6b Solving 13 + -9b = -17 + -6b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '6b' to each side of the equation. 13 + -9b + 6b = -17 + -6b + 6b Combine like terms: -9b + 6b = -3b 13 + -3b = -17 + -6b + 6b Combine like terms: -6b + 6b = 0 13 + -3b = -17 + 0 13 + -3b = -17 Add '-13' to each side of the equation. 13 + -13 + -3b = -17 + -13 Combine like terms: 13 + -13 = 0 0 + -3b = -17 + -13 -3b = -17 + -13 Combine like terms: -17 + -13 = -30 -3b = -30 Divide each side by '-3'. b = 10 Simplifying b = 10
| 11n=12n-18 | | 7k+10=9k | | 9/x+3-5/x-3=5x/x^2-9 | | (5k-6)/4=-5 | | -1-2f=6-f | | 10+8u-1=10u-7 | | Cos(37=11/x | | 5(3p+1)=50 | | 80x^2+52x+8=0 | | 9x+2/7x=6/7-4/x | | 3(3a+9)=0 | | 9x-.2y=4 | | -7x-6-7x=-118 | | 14-.5y=x | | 4/100=x/(4178.891+x) | | 5x^2-75x+50=0 | | −7/8−1/2s=−1/4 | | -3y+27=-15x | | 10-2*7+4= | | 5x3/2+(-9/4) | | 1/6|1/3(x-2/5)|=5/6(x+1/4) | | −7/8−1/2s=-14 | | 1/6[1/3(x-2/5)]=5/6(x+1/4) | | 9a^2+11x+4=0 | | 1/3x+1/4x=3/4x+1/3 | | 4p-5+2p=-17 | | -24=-9q+3 | | 0=t^2-6t-7 | | 7n+7=28 | | 1/2a+1/3a=-15 | | x/7=x/8-9 | | 1/2a+1/3a=2−17 |